Physical and Mechanical Properties of Ammonia-Treated Black Locust Wood - Stanciu Mariana Domnica; Sova Daniela; Savin Adriana; Ilias Nicolae; Gorbacheva Galina A. (MDPI AG, 2020)
Because of the uneven colour of black locust wood, different technologies are used to change the colour, the bestknown being chemical and thermal treatments. Some of them affect the mechanical properties of wood, such as elasticity modulus, strength, durability. This study aims to compare the physical and mechanical properties of black locust wood control samples and treated wood samples with ammonia hydroxide, in terms of density profile, colour values (CIE L*, a*, b*), mechanical properties of samples subjected to static bending, viscous-elastic properties (storage modulus (E’), loss modulus (E”) and damping (tanδ)). Two types of ammonia-fuming treatment were applied on samples: first treatment T1-5% concentration of ammonia hydroxide for 30 days; second treatment T2-10% concentration for 60 days. The results highlighted the following aspects: the overall colour change in the case of the second treatment is 27% in comparison with 7% recorded for the control samples; the lightness and yellowness values are the most affected by the second ammonia treatment of black locust wood. The density increased with almost 20% due to ammonium fuming (10% concentration/60 days); in case of static bending, the elastic modulus (MOE) tends to decrease with increasing the exposure time to ammonium, but the modulus of rupture (MOR) increases with almost 17% and the breaking force increases too, with almost 41%. In the case of dynamic mechanical analysis, the temperature leads to different viscous-elastic behaviour of each type of samples.
Keywords: black locust wood; ammonia treated wood; colour change; dynamic mechanical analysis